Health and Well-Being in India A Quantitative Analysis of Inequality in Outcomes and Opportunities - Borooah, Vani Kant (Springer International Publishing, 2018)
The theme of this book is health outcomes in India, in particular to outcomes relating to its caste and religious groups and, within these groups, to their women and children. The book's tenor is analytical and based upon a rigorous examination of recent data from both government and non-government sources. The major areas covered are sanitation, use by mothers of the government's child development services, child malnutrition, deaths in families, gender discrimination, and the measurement of welfare. .